A Critical Discourse Analysis of American ideologies embedded in some American online news on the conflicts in the South China Sea from 2014-2015 = phân tích diễn ngôn phê phán về hệ tư tưởng Mỹ trong các bản tin điện tử Mỹ về các cuộc xung đột - Quách, Hải Yến (2019)
This is a qualitative study that presents the findings of a linguistic analysis on American online news on the conflicts of the South China Sea from 2014-2015. The research has applied Fairclough‟s three-dimension framework and Halliday‟s Systemic functional grammar to identify and explain how American ideologies are portrayed and represented through language used in the American online news written by the American reporters. In this research the writer used the descriptive method to study the problem.